Effect of an exercise program on musculoskeletal symptoms and productivity: an ongoing study in an automotive industry - Santos, Joana (2014)
The ergonomic risk factors that can cause or aggravate musculoskeletal disorders include: repetitive awkward posture, forceful exertions, pressure points, and static postures. There is no doubt that the new forms of work led to greater ease and comfort in the lives of workers, but the need for increase specialization of workers, improving product quality and reducing production costs, leads to the appearance of various health problems, including work related musculoskeletal disorders (WRMSDs). There are evidences that performing regular physical activity reduces the risk of chronic diseases (Bairati, Larouche, Meyer, Moore, & Fradet, 2000). The implementation of physical activity programs at worksites has been increasingly common. Some studies indicate that these programs allows the prevention/reduction of manifestation of the injury, the normalization of body functions, promote relaxation and socialization between workers, improving working conditions and preparing the participants for their daily activities. However, no evidence was found to indicate an effect of physical activity programs on productivity (Proper, Staal, Hildebrandt, van der Beek & van Mechelen, 2002).